Marketing Analysis of Sangkuriang Catfish in Pokdakan Sindu Lestari, Bantuas Village, Palaran District, Samarinda City - Abdillah, Agung Faisail; Syafril, Muhammad; Fahrizal, Wahyu (Program Studi Budidaya Perairan Universitas Mataram, 2024)
Agung Faisal Abdillah, 2022. Marketing Analysis of Sangkuriang Catfish in Pokdakan Sindu Lestari, Bantuas Village, Palaran District, Samarinda City. (Supervised by M. Syafril and Wahyu Fahrizal) The purpose of this research is to know the pattern of the marketing channel for the sangkuriang catfish enlargement business and the marketing functions carried out at each marketing agency in the Pokdakan Sindu Lestari and to analyze the marketing performance of the sangkuriang catfish which includes margins, profits and farmer's share. This research is a quantitative descriptive research conducted using the case study method. The results obtained in this study are that the pokdakan sindu lestari marketing channel consists of 2 marketing channels, namely level zero marketing channel, level one marketing channel Marketing margin from producers to retailers is Rp. 6,000, the profit of all marketing channels is Rp. 4,266.49 kg. in one marketing process. And the marketing channel margin level one produces a farmer's share of 76%.